Gravidez não planejada : prevalência e fatores associados - Rodrigues, Alessandra Carreira (2016)
Pregnancy is a biologically natural event, and, according to the circumstances in which the woman becomes pregnant, it may have been planned or unplanned. Unplanned pregnancy is any gestation that was not envisaged by the couple or by the woman. Its occurrence has an important impact on the accomplishment of prenatal, maternal-infant health, and maternal and infant morbidity and mortality rates. Bearing in mind these aspects, the objective of this study was to analyze the prevalence and the aspects associated with the occurrence of unplanned pregnancy in the city of Cuiabá, Mato Grosso, Brazil. To that end, an epidemiological study, with quantitative approach and cross-sectional cohort was performed. The study participants were 385 puerperal women admitted to three hospitals located in Cuiabá/MT, aged between 18 and 45 years. Data collection took place by means of interviews, using a form composed of structured and semi-structured questions. The classification of pregnancy planning in planned, ambivalent and unplanned was obtained after applying the validated instrument London Measure of Unplanned Pregnancy (LMUP). The study period covered from May to August 2015. In order to analyze data, descriptive and inferential analyzes were performed, through the Epi-Info program, versions 3.5.2 and 7. The results are displayed in the form of two manuscripts. The first analyzed the prevalence and the factors associated with the occurrence of unplanned pregnancy in Cuiabá/MT. It was found that the prevalence was 39% for unplanned pregnancy, and the occurrence was analyzed by X2 test, which showed that the event has a strong association with the factors race/color, marital status, per capita income, age of first pregnancy, number of children that they had before and the schooling level of the father of the child. The second manuscript identified reasons mentioned by women, which fostered the occurrence of unplanned pregnancy in the city of Cuiabá/MT. The results showed that unplanned pregnancy takes place with a greater frequency among women inserted in an unfavorable socioeconomic context, and the contraceptive behavior diverges from the desire not to get pregnant. Among the reasons that fostered the occurrence of unplanned pregnancy, the most frequent were: poor perception of the risk of becoming pregnant, lack of knowledge about contraceptive methods, myths and taboos surrounding the perceptions of women about contraceptive methods, assignment of the responsibility of contraception to themselves, difficulty to adapt to the chosen method, aspects related to gender inequality, such as difficulties to negotiate the use of the method with the partner, failure in health care, among others. One can conclude that women involved in an unfavorable socioeconomic context have more difficulties to conduct the contraception in the desired way. In light of the foregoing, facts like recognizing the situations in which they are at risk of becoming pregnant, having access to the contraceptive method, acquiring correct information about the use of the method and stimulating the autonomy in women to better negotiate the use of the method with the partner are elements that may increase the consistent use of contraceptive methods. Thus, it is up to the health professionals to recognize the reproductive health needs of the assisted population, from a more comprehensive approach, which goes beyond the choice and availability of a contraceptive method.